2013
DOI: 10.54652/rsf.2013.v43.i1.115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intensity of Erosion and Natural Coverage of Tractor Roads in Post-Exploitation Period

Abstract: UDK 630*38:551.311.21          625.711.84:551.311.21 Tractor roads are often, due to un-implementation of appropriate rehabilitation measures, exposed to erosion processes of various intensity. These processes can be particularly expressed upon completion of forest harvesting works if natural conditions also have such character which favors intensification of erosion process. Intensification of erosion processes on tractor roads in post-exploitation period most often occur in cases when surface wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Our research has shown that relief change, rates of erosion, and net changes are much greater for road sections running atop conglomerates versus limestone. These results are consistent with those obtained by Bajrić et al (2013) and Fidelus‐Orzechowska et al (2018). The management of forest roads demands maintenance efforts focused on securing poorly resistant road sections via the use of highly resistant rock blocks.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our research has shown that relief change, rates of erosion, and net changes are much greater for road sections running atop conglomerates versus limestone. These results are consistent with those obtained by Bajrić et al (2013) and Fidelus‐Orzechowska et al (2018). The management of forest roads demands maintenance efforts focused on securing poorly resistant road sections via the use of highly resistant rock blocks.…”
Section: Discussionsupporting
confidence: 93%
“…Gullies and rills play a significant role in increasing material transport along the roadbed (Arnáez et al, 2004). The type of geological substrate and the degree to which the roads are reinforced with vegetation can both strongly affect the magnitude of erosion within different sections of the road (Bajrić et al, 2013; Jordán & Martínez‐Zavala, 2008; Martínez‐Zavala et al, 2008; Rice et al, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…But in practice it is almost the other way around... "the grade depends more on the evaluator than on the student's answer, so for the student it is more important who examines him than how well he knows the subject" (Bujas, Z.: Knowledge tests and the possibility of their use in school practice , own edition, Zagreb, 1943. ) Research aimed at determining the objectivity, reliability, sensitivity and validity of teachers as measuring instruments in the evaluation of school written assignments proves that teachers are weak measuring instruments [2,3].…”
Section: Introductionmentioning
confidence: 99%